The burden of mild asthma: Clinical burden and healthcare resource utilisation in the NOVELTY study. (August 2022) - Golam, Sarowar Muhammad; Janson, Christer; Beasley, Richard; FitzGerald, J Mark; Harrison, Tim; Chipps, Bradley; Hughes, Rod; Müllerová, Hana; Olaguibel, José María; Rapsomaniki, Eleni; Reddel, Helen K.; Sadatsafavi, Mohsen; et al.
Abstract: Background: Patients with mild asthma represent a substantial proportion of the population with asthma, yet there are limited data on their true burden of disease. We aimed to describe the clinical and healthcare resource utilisation (HCRU) burden of physician-assessed mild asthma. Methods: Patients with mild asthma were included from the NOVEL observational longiTudinal studY (NOVELTY; NCT02760329), a global, 3-year, real-world prospective study of patients with asthma and/or chronic obstructive pulmonary disease from community practice (specialised and primary care). Diagnosis and severity were based on physician discretion. Clinical burden included physician-reported exacerbations and patient-reported measures. HCRU included inpatient and outpatient visits. Results: Overall, 2004 patients with mild asthma were included; 22.8% experienced ≥1 exacerbation in the previous 12 months, of whom 72.3% experienced ≥1 severe exacerbation. Of 625 exacerbations reported, 48.0% lasted >1 week, 27.7% were preceded by symptomatic worsening lasting >3 days, and 50.1% required oral corticosteroid treatment. Health status was moderately impacted (St George's Respiratory Questionnaire score: 23.5 [standard deviation ± 17.9]). At baseline, 29.7% of patients had asthma symptoms that were not well controlled or very poorly controlled (Asthma Control Test score <20), increasing to 55.6% for those with ≥2 exacerbations in the previous year. In terms of HCRU, at least one unscheduled ambulatory visit for exacerbations was required by 9.5% of patients, including 9.2% requiring ≥1 emergency department visit and 1.1% requiring ≥1 hospital admission. Conclusions: In this global sample representing community practice, a significant proportion of patients with physician-assessed mild asthma had considerable clinical burden and HCRU. Highlights: Patients with physician-assessed mild asthma still have significant disease burden. Over 20% of patients experienced any exacerbation in the previous 12 months. Almost 10% of patients had one or more hospital or clinic visit for an exacerbation. Nearly 30% of patients had not well or very poorly controlled asthma symptoms. Many patients were prescribed medication consistent with more severe disease.